Evaluation of clinicopathological profile of subjects with intrauterine fetal death - Pandey, Sunil Kumar; Porwal, Surabhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Intrauterine foetal death is an immense emotional burden for everyone concerned specially in the last trimester. Therefore, it is very important to find out, what has happened. Evaluation of clinical and pathological profile of women presenting with intrauterine foetal death has evoked great interest among the obstetricians. Methods: The prospective observational study was conducted in the department of Obstetrics and Gynaecology N.S.C.B. Medical College Jabalpur during 1st June 2012 to 31st October 2013. A total of 155 intrauterine foetal death subjects admitted during this period were evaluated. Clinically and laboratory profile of subjects done. Histomorphology of placenta was performed in each case. Full HPR finding were then correlated with clinical and laboratory findings of subjects. Results: Poor vascularity of villi and fever were significantly associated (p<0.01). Hypertension and Convulsion and fibrinoid necrosis, syncytial knot and placental infarcts were significantly associated (p<0.001) Premature placenta is associated with cytotrophoblastic layer (p<0.01). Conversely post mature placenta is associated with calcification and infarction. (p<0.01). Conclusions: All placentae associated with foetal death have either gross or microscopic abnormalities. Present study is a step towards understanding and extrapolating the already known causes of intrauterine foetal death in the perspective of Jabalpur and its adjoining districts.